Book Review: An Islamic Model for Stabilization and Growth - Rusydiana, Aam Slamet (Ekonomi Islam Indonesia, 2025)
The repeated failure of structural adjustment programs (SAPs) and stabilization designed by the IMF and World Bank in developing countries has created an urgent need for an alternative economic paradigm. The book An Islamic Model for Stabilization and Growth by Adama Dieye (2020) offers a macroeconomic approach based on Islamic principles, emphasizing a risk-sharing mechanism instead of the risk-shifting that characterizes the conventional model. Through a case study of Senegal, the book demonstrates that applying the Islamic economic model can produce more sustainable economic stability, more inclusive growth, and enhanced social justice. This article elaborates on the conceptual ideas and empirical findings of the book and highlights its relevance for economic policy reform in Muslim and developing countries.